On Cyber Vulnerabilities Management in Critical Sectors: the Health Sector - Irina-Delia NEMOIANU (Bulletin of "Carol I" National Defense University, 2025)
The digitalisation of the Romanian health sector has accelerated significantly, especially in the aftermath of the COVID-19 pandemic, but this transition has amplified cybersecurity risks, exposing critical infrastructures and patient data to persistent threats. This study analyses the technical and non-technical vulnerabilities of the medical sector, based on both documentary research and a survey conducted among representatives of health institutions. The results highlight important challenges, ranging from the use of outdated software, shortages of specialised cybersecurity staff and significant variations in the level of maturity of cyber protection between public and private organisations. Given the diversity of challenges identified, the resilience of the health sector requires an integrated cybersecurity strategy, underpinned by technological investments, continuous training and coherent risk management policies.